Psychological Preparedness as a Component of Adolescent Disaster Readiness: Evidence from Secondary School Students in Yogyakarta - Novita Nirmalasari; Rizqi Wahyu Hidayati; Ike Wuri Winahyu Sari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Indonesia’s recurrent exposure to earthquakes, floods, landslides, and volcanic eruptions places adolescents in schools under continuous disaster risk. Preparedness, however, is not built on technical knowledge alone. The ability to regulate emotions, maintain a sense of control, and act with confidence during emergencies may shape how students translate knowledge into action. Despite this, psychological preparedness is rarely examined as a distinct and measurable construct in large student populations, particularly in high-risk regions. As a result, the psychological dimension of readiness often remains secondary within school-based disaster programs. This study examined the levels of psychological preparedness and general disaster preparedness among junior and senior high school students in Yogyakarta and analyzed the relationship between the two constructs. Method: A cross-sectional correlational design was applied. Of 760 invited students, 700 participated (response rate 92.1%) from five districts/cities. The Psychological Preparedness for Disaster Scale and the General Disaster Preparedness Scale were administered. Because the data were not normally distributed, Spearman’s Rho was used to assess correlation. An adjusted linear regression model was then performed to evaluate whether psychological preparedness remained associated with general preparedness after accounting for educational level, age, and gender. Result: Most students demonstrated moderate levels of psychological preparedness (67.0%) and general disaster preparedness (65.8%). Psychological preparedness showed a positive correlation with general preparedness (r = 0.254; 95% CI 0.17–0.33; p < 0.001), indicating a small-to-moderate association. After adjustment, psychological preparedness remained independently related to general preparedness (? = 0.23, p < 0.001; R² = 0.14). The magnitude of the association was modest, yet stable across demographic controls. Conclusion: Psychological readiness appears to function as one meaningful layer within adolescent disaster preparedness rather than as a dominant driver of behavior. In high-risk school contexts such as Yogyakarta, strengthening emotional regulation, perceived coping capacity, and decision-making confidence may complement technical training. Disaster education, therefore, may benefit from integrating psychosocial skill development alongside drills and hazard knowledge, while maintaining coordination between schools, families, and local disaster management agencies. Longitudinal and intervention-based research is needed to determine whether enhancing psychological preparedness leads to sustained behavioral improvements over time.